Persetujuan Pasangan Kawin Dalam Pengalihan Aset Digital - Nicolas Mario Gunawan; Abdul Salam (UNES Law Review, 2024)
Spousal Consent in the transfer of digital assets has not been specifically regulated in Indonesian laws and regulations. This raises questions regarding the urgency of this agreement compared to other transfers of assets that require spousal consent. This research was conducted on crypto asset buying and selling schemes as a new form of development of assets that are widely traded in Indonesia. In practice, buying and selling digital assets still uses digital platforms and is not accompanied by spousal consent. The research methodology used is a doctrinal research method with a descriptive-analytical research type. This research is based on secondary data through literature study in conjunction with applicable laws and regulations in Indonesia. This research aims to understand the existence of digital assets in Indonesian laws and regulations and the forms of asset transfer that require spousal consent in Indonesia to apply objects in the form of digital assets. Based on the research results, it was found that there is a legal vacuum regarding the regulation of spousal consent in buying and selling digital assets, so there is a need for a regulation that regulates spousal consent in joint property legal acts to guarantee legal certainty and the validity of digital asset transactions.